Amazon Backed File System: A Review - Malhotra, S; Bali, V (International Journal of Computer Sciences and Engineering, 2025)
Cloud Computing is one of the major emerging IT technologies and is highly promising in terms of resources provisioning, unlimited data storage, remote access to applications, easy data backup amenity etc. One of its emerging platforms is AWS S3. It provides storage for the web. It serves developers/users with easy web-scale computing platform. This platform is reliable, scalable, inexpensive and efficient and provides persistent cloud storage. Amazon S3 and amazon.com share common scalable storage root in terms of their infrastructure. The data here is stored in fundamental containers called buckets. A bucket has the capacity to store limitless data. Infinite objects can be stored in a bucket, with each object being able to store a maximum of 5 TB of data. These objects require a unique developer-assigned key to be stored and retrieved by the developers. The data stored this way can be downloaded any instant of time by any user. Permissions to upload or download data to one’s own bucket can be granted or denied. The web service always keeps the data secure from unauthorized access using its invulnerable authentication mechanism. Various operations can be executed through the API such as Read an object, delete an object, list keys etc. Amazon S3 associates REST and SOAP API interfaces.